Prospective Validation of a Screening Tool to Identify Older Adults in Need of a Driving Evaluation. Issue 2 (12th December 2017) - Betz, Marian E.; Haukoos, Jason S.; Schwartz, Robert; DiGuiseppi, Carolyn; Kandasamy, Deepika; Beaty, Brenda; Juarez‐Colunga, Elizabeth; Carr, David B.
Abstract : Objectives: To prospectively validate and refine the 5‐item "CRASH" screening tool for identifying older drivers needing a behind‐the‐wheel (BTW) test. Design: Prospective observational study. Setting: Geriatric and internal medicine primary care clinics affiliated with a tertiary care hospital and a local BTW program. Participants: Cognitively intact drivers aged 65 and older (N = 315). Measurements: Participants completed baseline questionnaire (including CRASH tool) and assessments and BTW test (evaluator blinded to questionnaire results) and participated in 1‐month telephone follow‐up. Analysis included descriptive statistics and examination of predictive ability of the CRASH tool to discriminate normal (pass) from abnormal (conditional pass or fail) on the BTW test, with logistic regression and CART techniques for tool refinement. Results: Two hundred sixty‐six participants (84%) had a BTW test; of these, 17% had a normal rating and 83% an abnormal rating. Forty‐five percent of those with an abnormal score were advised to limit driving under particular conditions. Neither the CRASH tool nor its individual component variables were significantly associated with the summary BTW score; in refined models with other variables, the best‐performing tool had approximately 67% sensitivity and specificity for an abnormal BTW score. Most participants found the BTW test useful and were willing to pay a median of 50. At 1‐month follow‐up, no participants had stopped driving. Conclusion: The CRASH screening tool cannot be recommended for use in clinical practice. Findings on older adults' perceived utility of the BTW test and the stability of driving patterns at 1‐month follow‐up could be useful for future research studies and for design of older driver programs.